Differential pattern of RP1 mutations in retinitis pigmentosa - Zhang, Xin (Molecular Vision, 2010)
PURPOSE: Retinitis pigmentosa 1 (RP1) is a major gene responsible for both autosomal dominant and autosomal recessive retinitis pigmentosa (RP). We have previously identified three disease-causing mutations out of 174 RP patients. In this study, we investigated a new cohort of Chinese RP patients to further evaluate the contribution of RP1 mutations to cause RP. METHODS: A group of 55 nonsyndromic RP patients, the majority of them isolated cases or without information on family history, were screened for mutations in the entire coding sequences of RP1, using direct DNA sequencing. All detected variants were genotyped in 190 controls, while the three putative mutations were additionally genotyped in 362 controls subjects. Web-based programs, including PolyPhen, Sorting Intolerant from Tolerant (SIFT), Prediction of Pathological Mutations (PMUT), Single Amino Acid Polymorphism Disease-Association Predictor (SAP), ScanProsite, and ClustalW2, were used to predict the potential functional and structural impacts of the missense variants on RP1. RESULTS: A total of 14 sequence changes were identified. Among them, five were novel and found only in the RP patients. Two missense variants (p.K1370E and p.R1652L), which are conserved in primates, were predicted to have functional and structural impacts on the RP1 protein. The other three variants (c.787+34T>C, p.I408L and p.L2015L) were considered benign. CONCLUSIONS: If these two novel missense variants are in fact pathogenic, then RP1 mutations account for approximately 2.18% (5/229) of RP cases in our Chinese cohort; this is similar to other ethnic groups. However, a relatively higher frequency of missense mutations found in the Chinese patients may suggest an ethnic diversity in the RP1 mutation patterns.